TIME HISTOGRAMS WITH INTERACTIVE SELECTION OF TIME UNIT AND DIMENSION - Savoska, Snezana; Loshkovska, Suzana; Blazeski, Vlatko (My University, 2008)
Many researchers are working on the improvement of the usability and efficiency of the sale data analysis methods which are required by the users – analytical staff and managers. In this paper, we present the improved technique of time histograms. We named proposed method Time Histograms with Interactive Selection of Time Unit and Dimension (THISTUD). Performed modifications and developed interactive user interface are described. The system is tested on the data warehouse that includes data for the ten years. The created sale data mart and visualization results are presented in the paper too.